PERAN ORANGTUA TERHADAP ANAK - Sunardin Sunardin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Abstract: Sunardin, The Role of Parents Towards Children. This study aims "Parents play a very important role in the lives of their children. Since birth, children are very dependent on parents to meet their basic needs, such as food, clothing, and shelter. However, the role of parents is not only limited to meeting basic needs. Parents also play a role in shaping the character, abilities, and future of their children. According to Hamalik (2011), a role is a certain pattern of behavior that is characteristic of all officers from a particular job or position. Through affection, support, and guidance, parents can help their children grow and develop into balanced and accomplished individuals. According to Willis (2010), parents are the father and mother of a child both through biological and social relationships. Parents are older people who are given the responsibility to care for and educate their children to become adults.